CADRE INSTITUTIONNEL ET ORGANISATIONNEL DE LA MISE EN OEUVRE DE LA GESTION COMMUNAUTAIRE DE LA FORET DES MARAIS TANOE-EHY AU SUD-EST DE LA COTE D’IVOIRE : FORCES ET CONTRAINTES. - Zadou Didié Armand; Kone Inza; Ibo Guéhi Jonas (European Scientific Journal, ESJ, 2012)
After walking surveys conducted in the Ivorian forests in 2004, the Tanoe-Ehy Forest (TEF) has been identified by the Program of Research and Actions for the Safeguard of Primates in Côte d'Ivoire (RASAP-CI) as a site of high conservation value. Despite its importance in terms of biological, socio-economic, cultural and ecological aspects, the forest is subject to strong anthropogenic pressures that result in poaching, uncontrolled harvesting of natural resources and agricultural land clearing attempts. With the aim of a sustainable conservation of TEF, a pilot program of community management is initiated with local communities of Tanoe-Ehy space in September 2006. The steps to give the official protection status of this forest, namely the status of Voluntary Nature Reserve (VNR), are underway. The institution of the community management of TEF in Tanoe-Ehy space, if it leads, will be the first experiment of its kind in Côte d’Ivoire. So, how is characterized the institutional and organizational framework of the implementation of this community management? This article aims to describe the institutional and organizational framework of the implementation of the community management program of TEF and analyze, in « SWOT » approach, this program to detect strengths and opportunities, but also some weaknesses and threats. This work demonstrates that the implementation of the community management of TEF present a coherent institutional and organizational framework which is determinant for the outcome of the process.